If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -4t = 5t + -21 Reorder the terms: 6 + -4t = -21 + 5t Solving 6 + -4t = -21 + 5t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5t' to each side of the equation. 6 + -4t + -5t = -21 + 5t + -5t Combine like terms: -4t + -5t = -9t 6 + -9t = -21 + 5t + -5t Combine like terms: 5t + -5t = 0 6 + -9t = -21 + 0 6 + -9t = -21 Add '-6' to each side of the equation. 6 + -6 + -9t = -21 + -6 Combine like terms: 6 + -6 = 0 0 + -9t = -21 + -6 -9t = -21 + -6 Combine like terms: -21 + -6 = -27 -9t = -27 Divide each side by '-9'. t = 3 Simplifying t = 3
| x^2-19x-6=0 | | 2(-12+15x)=3(10x-8) | | 2v^2+17v+39=(v+7)(v+7) | | h+9.7= | | (3a+9)=(8a+9) | | 2y-17=3x-8 | | 130b=-355 | | y=0.8x+2.8 | | r(z^7+9)+(Z^7+9)= | | y=ln(x^2-14x) | | x^3-3x=4 | | -35=1-4h | | 0.12x+0.8(x-2)=0.01(5x-4) | | (7x+9)(x^2+6x+8)= | | 3(3x+9)-2x=4x | | 9w+w+7=57 | | -192a=-1359 | | (7x+9)(x^2+6x+8)=0 | | 42-6x=10-10x | | 6x-42=10-10x | | .75(24-6b)=10b+2 | | 50=350*R*1.5 | | 2x+10=7x-30 | | -2.25b-8=6.5 | | 6b+53=89 | | -2x+6=6x-2 | | 5x-2(7x+6)=16-9x | | 6x+15y=10600 | | 6y^2-3y+4y^2-5y= | | -7m=-490 | | y=0.29x+13 | | 9x^2+25=19 |